Partner selection for reverse logistics centres in green supply chains: a fuzzy artificial immune optimisation approach. Issue 16 (9th December 2016) - Wu, Chong; Barnes, David
Abstract: The design of reverse logistics networks has now emerged as a major issue for manufacturers, not only in developed countries where legislation and societal pressures are strong, but also in developing countries where the adoption of reverse logistics practices may offer a competitive advantage. This paper presents a new model for partner selection for reverse logistic centres in green supply chains. The model offers three advantages. Firstly, it enables economic, environment and social factors to be considered simultaneously. Secondly, by integrating fuzzy set theory and artificial immune optimisation technology, it enables both quantitative and qualitative criteria to be considered simultaneously throughout the whole decision-making process. Thirdly, it extends the flat criteria structure for partner selection evaluation for reverse logistics centres to the more suitable hierarchy structure. The applicability of the model is demonstrated by means of an empirical application based on data from a Chinese electronic equipment and instruments manufacturing company.